Effects of Dietary Amino Acid Density and Exogenous Protease Inclusion on Growth Performance and Apparent Ileal AA Digestibility in Broilers - Haley K. Wecker; Courtney N. Truelock; Christopher J. Delfelder; Caitlin E. Evans; Renan A. Donadelli; Charles G. Aldrich; Miguel A. Barrios; Charles R. Stark; Robert S. Beyer; John M. Gonzalez; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
Protein is one of the most expensive nutrients in poultry diets. In an effort to minimize feed costs, protein digestion and utilization by the animal must be carried out as efficiently as possible. Therefore, the objective of this study was to evaluate the effects of dietary AA density and exogenous protease inclusion on growth performance and AA digestibility in broilers. Treatments consisted of a 2 × 4 factorial design with main effects of commercial protease (with or without) and digestible Lys (1.12, 1.15, 1.18, or 1.21%). Broiler chicks were housed in 4 Petersime batteries and treatments were randomly assigned to 80 cages within location block, resulting in 10 cages per treatment with 6 chicks per cage at placement. A commercial enzyme complex with 3 proteolytic activities was added to the protease diets at 0.25 lb/ton, and the same inclusion of sand was added to the diets without protease. Diets were balanced by energy and Lys:amino acid ratios. Titanium dioxide was included in the diets at 0.5% as an indigestible marker. On d 20, ileal contents from 2 chicks per cage were collected and composited by cage for calculation of apparent ileal AA digestibility. Growth performance metrics were calculated from cage weights and feed consumption was recorded throughout the experiment, and AA digestibility data were obtained from analysis of ileal contents. Data were analyzed using SAS 9.4 with cage as the experimental unit and cage location as the blocking factor. There was no evidence of an amino acid density × protease interaction (P>0.05) for BW, ADG or ADFI. There was an amino acid density × protease interaction (quadratic,P<0.05) for feed conversion ratio (FCR). Chicks fed 1.12 and 1.21% digestible Lys diets with added protease had a 2-point improvement in FCR compared to chicks fed these diets without protease. There was no difference in FCR between birds consuming diets with or without protease when fed 1.15 and 1.18% digestible Lys diets. There was no evidence of difference (P>0.10) in ADG or ADFI due to dietary amino acid density throughout the feeding period. However, broiler FCR was improved (linear,P<0.01) by increasing dietary amino acid density from 1.12 to 1.21% digestible Lys. There was no evidence (P>0.10) of main effect of added protease on BW, ADG, ADFI, or FCR. There was not an amino acid density × protease interaction (P>0.09) or main effect of dietary amino acid density or protease inclusion (P>0.12) on apparent ileal digestibility (AID) of Lys, Arg, Met, Cys, Thr, Ile, Leu, Val, or Trp. In conclusion, increasing dietary amino acid density improved FCR in broiler chicks, and the rate of improvement was dependent on the inclusion of an exogenous protease.
Keywords: amino acids; broilers; digestibility; poultry; protease